Bevacizumab in advanced lung cancer: state of the art. (December 2017) - Assoun, Sandra; Brosseau, Solenn; Steinmetz, Christelle; Gounant, Valérie; Zalcman, Gérard
Despite recent advances in metastatic lung cancer treatment with the advent of immune checkpoint inhibitors and molecules targeting addictive genomic abnormalities, prognosis of most of the patients remains unfavorable. Combination approaches with older drugs, such as bevacizumab, should be thus envisioned. Bevacizumab is a monoclonal anti-VEGF antibody, approved by the US FDA and the EMA in first-line and maintenance settings of advanced nonsquamous non-small-cell lung cancer (NSCLC) treatment, in association with platinum-based chemotherapy. In the years to come, bevacizumab might be associated with new molecular therapies or immuno-oncology drugs, in order to optimize response rates and overcome resistances. This review summarizes the pharmacologic properties, clinical efficacy and safety of bevacizumab in advanced lung cancer treatment, with a focus on NSCLC, EGFR -mutant NSCLC and small-cell lung cancer.